Catalytic Aerobic Oxidations 2020
DOI: 10.1039/9781839160332-00016
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation Reactions Using Metal-based Homogeneous Systems

Abstract: Molecular oxygen is the reagent of choice for many organic reactions, including the oxidation of a variety of substrates. The importance of carbonyl and carboxylic compounds has boosted research on alternative approaches based on more sustainable reagents. To this end, aerobic oxidative approaches have emerged as a promising option to other entries involving Friedel-–Crafts acylation, Claisen condensation, esterification or amidation reactions. In comparison with the use of heterogeneous catalysts and organoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 250 publications
0
1
0
Order By: Relevance
“…Chemoselective catalytic oxidation of alcohols is a powerful strategy for the sustainable production of fine and commodity chemicals with minimal time, waste, and cost. Air is a convenient and attractive terminal oxidant, but partially reduced oxygen can generate highly active species that participate in competitive, nonselective reactions. , We previously reported that the dimeric cationic palladium complex [( L 1 )­Pd­(μ-OAc)] 2 [OTf] 2 ( L 1 = neocuproine = 2,9-dimethyl-1,10-phenanthroline) is an effective catalyst precursor for the oxidation of vicinal polyols under mild conditions to afford α-hydroxyketones with high regio- and chemoselectivities. This catalyst is also selective for the direct oxidation of carbohydrates to 3-ketoses, , a complex transformation that typically demands multiple steps of protection/deprotection. , However, under aerobic conditions, H atom abstraction and subsequent oxidation of the benzylic methyl C–H bonds on the neocuproine ligand generate inactive palladium carboxylate species (Figure A, species 1** ). ,, This competitive ligand oxidation limits catalyst lifetime and necessitates high palladium loadings to achieve high conversions.…”
Section: Introductionmentioning
confidence: 99%
“…Chemoselective catalytic oxidation of alcohols is a powerful strategy for the sustainable production of fine and commodity chemicals with minimal time, waste, and cost. Air is a convenient and attractive terminal oxidant, but partially reduced oxygen can generate highly active species that participate in competitive, nonselective reactions. , We previously reported that the dimeric cationic palladium complex [( L 1 )­Pd­(μ-OAc)] 2 [OTf] 2 ( L 1 = neocuproine = 2,9-dimethyl-1,10-phenanthroline) is an effective catalyst precursor for the oxidation of vicinal polyols under mild conditions to afford α-hydroxyketones with high regio- and chemoselectivities. This catalyst is also selective for the direct oxidation of carbohydrates to 3-ketoses, , a complex transformation that typically demands multiple steps of protection/deprotection. , However, under aerobic conditions, H atom abstraction and subsequent oxidation of the benzylic methyl C–H bonds on the neocuproine ligand generate inactive palladium carboxylate species (Figure A, species 1** ). ,, This competitive ligand oxidation limits catalyst lifetime and necessitates high palladium loadings to achieve high conversions.…”
Section: Introductionmentioning
confidence: 99%